2016
DOI: 10.1021/acs.jafc.6b00438
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Prunus spp. Cyanide Seed Defense System onto Wheat: Reduced Insect Feeding and Field Growth Tests

Abstract: Many crops are ill-protected against insect pests during storage. To protect cereal grains from herbivores during storage, pesticides are often applied. While pesticides have an undoubtable functionality, increasing concerns are arising about their application. In the present study, we investigated a bioinspired cyanogenic grain coating with amygdalin as cyanogenic precursor mimicking the feeding-triggered release of hydrogen cyanide (HCN) found for example in bitter almonds. The multilayer coating consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Seed size constitutes an important agricultural trait. In agricultural crops, large seed size not only indicates yield enhancement but also suggests the enhancement of other merits, for example, seed biotinylated protein, 36 seed protein and oil, 5 seed defense, 37 blueberry seed oils, 38 and sugar beet seed. 39 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Discussionmentioning
confidence: 99%
“…Seed size constitutes an important agricultural trait. In agricultural crops, large seed size not only indicates yield enhancement but also suggests the enhancement of other merits, for example, seed biotinylated protein, 36 seed protein and oil, 5 seed defense, 37 blueberry seed oils, 38 and sugar beet seed. 39 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, in some experiments, researchers have attempted to produce seeds containing cyanogenic multilayers for use as protective coatings (biodegradable polylactic acid, amygdalin, or β-glucosidase). Gaseous HCN is released only when protective layers are ruptured by a herbivore attack [ 68 ]. Rajendran and Sriranjini [ 66 ] and Campolo et al [ 69 ] showed that the array of natural botanical substances (e.g., essential oils) exhibiting insect toxicity in the vapor phase is much wider than that of synthetic substances, but the extent of their current practical use is profoundly narrower.…”
Section: Gas and Vapor Insecticide Application Formulationsmentioning
confidence: 99%
“…The extract of Solanum nigrum fruits exerted only sublethal effects on mealworms by disrupting their development and metabolism. When combined with other pest management strategies, these extracts could offer a cheap, effective and environmentally-friendly solution to crop protection [180,181].…”
Section: Contaminantsmentioning
confidence: 99%